John Tibbit correspondence and indenture - Tibbit, John.
Letterbook containing indenture and correspondence (1789-1797) between Tibbitt and Alexander Macomb relating to land in New York. Includes a letter (1927 November 16) of Caroline Bacon.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bacon, Caroline -- Correspondence; Macomb, Alexander, -- 1748-1831 -- Correspondence; Deeds -- New York (State); Land tenure -- New York (State)